Numerical and experimental investigation of Joule heating in a carbon fibre powder epoxy towpregging line. (January 2023) - Çelik, Murat; Maguire, James M.; Noble, Thomas; Robert, Colin; Ó Brádaigh, Conchúr M.
Abstract: Powder epoxy based towpregs offer favourable processing and storage properties, thanks to the low viscosity and thermal stability of the powder epoxy. Low-cost, high-quality towpregs, which are suitable for automated fibre placement or filament winding applications, can be produced at a high production rate with an automated towpregging line. This study focuses on improving the towpregging process by analysing the heating characteristics of a towpregging line that employs Joule heating to impregnate carbon fibre tows with powder epoxy. A finite element analysis heat transfer model was developed to identify the relationship between processing parameters and heating of the carbon fibre tows. Model predictions matched well with experimental results. Using the temperature distribution predicted by the model, powder epoxy melting and sintering behaviour was investigated using semi-empirical equations. Results revealed that Joule heating provides efficient heating with very low power consumption. It was found that while it is possible to produce towpregs at high production speeds (15 m/min), slower speeds might yield more consistent quality. Using parametric studies in the model, it was shown that it is possible to increase towpregging line production rate without compromising the towpreg quality, by altering some of the key process parameters (supplied current, electrode distance etc.).